Treatment-Specific Hippocampal Subfield Volume Changes With Antidepressant Medication or Cognitive-Behavior Therapy in Treatment-Naive Depression - Tai, Hua-Hsin; Cha, Jungho; Vedaei, Faezeh; Dunlop, Boadie W.; Craighead, W. Edward; Mayberg, Helen S.; Choi, Ki Sueng (Frontiers in Psychiatry, 2021)
Background: Hippocampal atrophy has been consistently reported in major depressive disorder. However, literature on hippocampal volume changes after antidepressant treatment has been limited. The first-line treatments for depression include antidepressant medication (ADM) or cognitive-behavior therapy (CBT). The effects of these treatments on hippocampal subfield volume changes are unclear. To understand the differential effects of CBT and ADM on the hippocampus, we investigated the volume alterations of hippocampal subfields with treatment and outcome in treatment-naïve depression patients. Methods: Treatment-naïve depressed patients from the PReDICT study were included in this analysis. A total of 172 patients who completed 12 weeks of randomized treatment with CBT (n=45) or ADM (n=127) were included for hippocampal subfield volume analysis. Forty healthy-controls were also included for the baseline comparison. Freesurfer6.0 was used to segment 26 hippocampal substructures and bilateral whole hippocampus. A generalized linear model with covariates of age and gender was used for group statistical tests. A linear mixed model for the repeated measures was used to examine volumetric changes over time and the contributing effects of treatment type, outcome, and illness chronicity. Results: Of the 172 patients, 85 achieved remission (63/127 ADM, 22/45 CBT). MDD patients showed smaller baseline volumes than controls in CA1, CA3, CA4, parasubiculum, GC-ML-DG, Molecular-layer, HATA, and fimbria. Over 12 weeks of treatment, further declines in the volumes of CA1, fimbria, subiculum, and HATA were observed regardless of treatment type or outcome. Notably, CBT remitters showed volume reduction in the right hippocampal tail, which did not occur in ADM remitters. Unlike ADM remitters, ADM nonresponders had a decline in volume in the bilateral hippocampal tails. Baseline volume of left presubiculum (regardless of treatment type) and right fimbria and HATA in CBT patients were correlated with a continuous measure of clinical improvement. Conclusion: Differential treatment-specific volume changes in the hippocampal tail after 12 weeks of treatments. This finding suggests that remission achieved via ADM may protect against progressive hippocampal atrophy by altering neuronal plasticity or inducing neurogenesis. Studies with multimodal neuroimaging, including functional and structural analysis, are needed to assess further the impact of two different antidepressant treatments on hippocampal subfields.